COMPREHENSIVE SCHOOL IN THE CONTINUUM OF LIFELONG LEARNING: ROLE, FUNCTIONS, AND INSIGHT OF ITS REALIZATION - Bartaševičius, Robertas (Acta Paedagogica Vilnensia, 2014)
The article analyzes the role a comprehensive school has in the continuum of lifelong learning. Based on the theoretical insights of foreign authors (such as N. Longworth, J. Chapman, D. Aspin, J. Bryce, W. K. Davies and others), the functions a school willing to contribute to the fulfilment of the idea of lifelong learning in the educational environment could take on and/or carry out are discussed. Particular attention is paid to modelling the pedagogical system and its elements in a lifelong school, emphasizing that the essential and main activities of a comprehensive school are education. The article describes the features should a teacher and students of a lifelong school possess, the requirements set for the content, methods, forms and means of education. The conclusion is made that the comprehensive school lays the foundation of lifelong learning: a positive attitude towards learning is formed, the learning motivation is strengthened, the reasons for unwillingness to learn are eliminated, etc. It is also stated that the role of comprehensive school in fulfiling the idea of lifelong learning is extremely important and related to different areas of school activities (school management, relationship with the community, school culture, etc.). Bearing in mind the challenges of lifelong learning, the pedagogical system of a school should also be modelled with a methodological access of a student-oriented educational paradigm. The article introduces one of the possibilities to fulfill the ideas of lifelong learning on the institutional level of education reality – to form and to carry out a school-level education policy oriented towards the theoretical conceptualization and practical realization of the pedagogical system.